IMPROVING STUDENTS’ READING COMPREHENSION USING COOPERATIVE LEARNING - STAD METHOD AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 KERUAK IN THE ACADEMIC YEAR OF 2012/2013 - ARI SAPUTRA (LPPM Universitas Gunung Rinjani, 2020)
Penelitian tindakan kelas ini dilakukan pada kelas sebelas program studi IPS SMA Negeri 1Keruak. Penelitian tindakan kelas ini bertujuan untuk mengetahui bagaimana metode CLSTADmeningkatkan pemahaman membaca siswa yang termasuk pada mengenalkanproses dan hasil dari pembelajaran menggunakan metode ini. Untuk identifikasi proses,peneliti mengamati semangat siswa, aktifitas individu dan kelompok siswa ketika prosespembelajaran. Pada siklus pertama, didapatkan siswa dengan semanga yang rendah, kerjakelompok tidak efektif, dan beberapa siswa mengabaikan aturan tugas individu. Ketikamelakukan siklus kedua, mereka terlihat sangat bersemangat, kerja kelompok menjadi lebihefektif dan masing-masing iswa mengerjakan tugas individu dengan percaya diri. Jumlahsiswa yang mencapai standar penguasaan pembelaran yaitu 70%, naik dari siklus pertamake siklus kedua. Ini membuktikan bahwa hasil tes dari 8 (32%) dari 25 siswa yang mencapaipenguasaan standar pada siklus pertama menjadi 19 siswa (76%) pada siklus kedua.Dengan kata lain, kelas tersebut berhasil mencapai penguasaan standar belajar. Ini berartipencapaian pemahaman membaca siswa benar-benar bertambah dengan menggunakanmetode CL-STAD.Kata Kunci: Membaca, belajar kelompok, STAD.This Classroom Action Research was conducted at the eleventh grade of SMA Negeri 1Keruak. This classroom action research is aimed at finding out how CL – STAD methodimprove students’ reading comprehension which implies at identifying the process and theresult of teaching learning using the method. To identify the process, the researcherobserved students’ enthusiasm, students’ cooperative and individual activities while teachinglearning process. In the first cycle, it was found that the students were less enthusiastic yet,the cooperative work was not effective, and some of them ignored the role of individual task.When conducting the second cycle, they seemed very enthusiastic, the cooperative workbecame more effective, and each student did his individual task confidently. While thenumber of students who reached the mastery learning standard, 70 %, increased from thefirst to the second cycle. It is proved by the result of the tests that from 8 (32 %) of 25students who gained the mastery learning standard in the first cycle became 19 (76 %)students in the second cycle. In other words, the class was successfully reached the masterylearning standard. It means that students’ reading comprehension achievement is trulyimproved by the use of CL – STAD Method.Keywords: Reading, Cooperative learning, STAD.